2019
DOI: 10.1186/s13014-019-1208-1
|View full text |Cite
|
Sign up to set email alerts
|

Direct radiation-induced effects on dental hard tissue

Abstract: BackgroundRadiation caries is a complication of radiotherapy characterized by enamel erosion and dentin exposure. The mechanisms of characteristic radiation caries formation are not well-understood. The aim of this study was to evaluate the direct radiation-induced effects on dental hard tissue and investigate their role in the formation of radiation caries.MethodsSixty non-carious third molars were divided into three groups (n = 20), which would be exposed to 0 Gy, 30 Gy, and 60 Gy radiation, respectively. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
56
1
21

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 32 publications
(48 reference statements)
8
56
1
21
Order By: Relevance
“…e radiation dose, the localization of the tumor, and the sensitivity of the normal tissue next to the tumor are all factors affecting the severity of adverse effects to RT [5]. RT may cause xerostomia, dysphagia, mandibular osteoradionecrosis, trismus, hearing loss, and radiation caries [5,9].…”
Section: Introductionmentioning
confidence: 99%
“…e radiation dose, the localization of the tumor, and the sensitivity of the normal tissue next to the tumor are all factors affecting the severity of adverse effects to RT [5]. RT may cause xerostomia, dysphagia, mandibular osteoradionecrosis, trismus, hearing loss, and radiation caries [5,9].…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al 12 and Gonçalves et al 4 determined a decrease in the enamel microhardness close to the DEJ region, while de Siqueria et al 10 determined rst a decrease and then an increase. As for the dentin, while Gonçalves et al 4 found a decrease in the microhardness close to the DEJ region after radiation, de Siqueria et al 10 rst found a decrease and then an increase.…”
Section: Discussionmentioning
confidence: 99%
“…4,10 Because of the increasing amount of organic structure in the DEJ region, this region was stated to be affected more by radiotherapy than the other regions. 4,10,12,14 It was reported that the enamel and dentin hardness values increased depending on the point of the measurement, and the hardness value when moved away from the DEJ region. 25 In our study, the measurements were made from the enamel and dentin regions 50 µm away from the DEJ region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations